Lifetime antimicrobial use is associated with weight status in early adolescence—A register‐based cohort study. Issue 3 (21st September 2020) - Figueiredo, Rejane Augusta de Oliveira; Kajantie, Eero; Neuvonen, Pertti J.; Rounge, Trine B.; Weiderpass, Elisabete; Viljakainen, Heli
Summary: Background: Antimicrobial agents (AMs) are the most prescribed drugs to children. Early and repeated exposure to AMs in infancy is associated with increased risk of childhood overweight and obesity. Aims: We extended the investigation of AMs use, from birth to early adolescence, and evaluated their association with weight status. Materials & Methods: A total of 10093 children from Finnish Health in Teens cohort (Fin‐HIT) with register‐based data on AMs purchases and measured weight status at the mean age of 11.2 y (SD 0.82) were included in the study. The key exposures were the number AM purchases at a given age or the sum of these during the entire follow‐up time to describe lifetime exposure / use. Outcome was weight status in early adolescence defined with International Obesity Task Force cut‐offs for the age‐ and sex‐specific body mass index. Odds Ratio (OR) and 95% confidence intervals (CI) were estimated using Multinomial Logistic Regression. Results: Of children, 73.7% were normal weight, 11.1% thin and 15.2% overweight/obese. AMs use was highest during the second year of life, when 65% of all children used AMs, but thereafter decreased with age. The highest mean purchases and prevalence at any given age along with the highest lifetime use were consistently seen among overweight children. Each episode of AMs use throughout life increased the risk of being overweight in adolescence [OR = 1.02 (1.02–1.03)]. However, there was an inverse association between AMs use and thinness [OR = 0.98 (0.97–0.99)]. Discussion: Despite a high prevalence of AMs use during the early years, lifetime‐use was associated with weight status in early adolescence in a dose response manner. Conclusion: Future studies should address mechanisms underlying the relationship between AM use and weight.